2018
DOI: 10.1021/acsami.7b18889
|View full text |Cite
|
Sign up to set email alerts
|

Bactericidal and Hemocompatible Coating via the Mixed-Charged Copolymer

Abstract: Cationic antibacterial coating based on quaternary ammonium compounds, with an efficient and broad spectrum bactericidal property, has been widely used in various fields. However, the high density of positive charges tends to induce weak hemocompatibility, which hinders the application of the cationic antibacterial coating in blood-contacting devices and implants. It has been reported that a negatively charged surface can reduce blood coagulation, showing improved hemocompatibility. Here, we describe a strateg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
47
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 75 publications
(47 citation statements)
references
References 49 publications
0
47
0
Order By: Relevance
“…When it comes to the propensity to traverse or adhere to the biological barriers, including the cell wall and plasma membrane, negative surface charge is a hindrance, especially against phospholipid bilayers inherently incompatible with the hydrophilic nature of CPs, comprising two relatively highly charged ionic species: divalent calcium and trivalent phosphate. Although cationic surfaces tend to have more pronounced antibacterial properties, 36 combining cationic and anionic species on the surface, such as those present on the surface of CP, can retain the antibacterial efficacy while regaining better tissue compatibility, 37 and this duality is exactly the strength of CPs. Zwitterionic surfaces, in fact, are known for their excellent antifouling properties, which they owe to the tight hydration shells formed around charged groups.…”
Section: B Surface Chargementioning
confidence: 99%
“…When it comes to the propensity to traverse or adhere to the biological barriers, including the cell wall and plasma membrane, negative surface charge is a hindrance, especially against phospholipid bilayers inherently incompatible with the hydrophilic nature of CPs, comprising two relatively highly charged ionic species: divalent calcium and trivalent phosphate. Although cationic surfaces tend to have more pronounced antibacterial properties, 36 combining cationic and anionic species on the surface, such as those present on the surface of CP, can retain the antibacterial efficacy while regaining better tissue compatibility, 37 and this duality is exactly the strength of CPs. Zwitterionic surfaces, in fact, are known for their excellent antifouling properties, which they owe to the tight hydration shells formed around charged groups.…”
Section: B Surface Chargementioning
confidence: 99%
“…More recently, a bactericidal and hemocompatible coating was engineered by using mixed‐charged copolymer of poly(quaternized vinyl pyridine‐ co ‐ n ‐butyl methacrylate‐ co ‐methacrylate acid), namely P(QVP‐ co ‐ n BMA‐ co ‐MAA), via ultrasonic spraying technique on versatile surfaces such as glass or polyethylene terephthalate ( Figure ) . The P(QVP‐ co ‐ n BMA‐ co ‐MAA) copolymer was synthesized via free radical copolymerization and subsequent quaternization and deprotection of the carboxyl groups.…”
Section: Multifunctional Antibacterial Materialsmentioning
confidence: 99%
“…Schematic illustration of the molecular structure of P(QVP‐ co ‐ n BMA‐ co ‐MAA) copolymer and the resultant surface coating. Reproduced with permission . Copyright 2018, American Chemical Society.…”
Section: Multifunctional Antibacterial Materialsmentioning
confidence: 99%
“…Mixed‐charge polymers have been proved to be novel candidates of antifouling materials. Our group developed a mixed‐charge poly(quaternized vinyl pyridine‐co‐n‐butyl methacrylate‐co‐methacrylate acid) (P(QVP‐co‐nBMAco‐MAA)) coating, which showed resistance to nonspecific adsorption of proteins and therefore improved the hemocompatibility of the surface (Fan et al, ). Venault et al () reported poly(vinylidene fluoride) membranes that modified by the mixed‐charge copolymer of [2‐(methacryloyloxy) ethyl]trimethylammonium and sulfopropylmethacrylate.…”
Section: Mixed‐charge Polymermentioning
confidence: 99%